PENGARUH LITERASI KEUANGAN DAN PENGGUNAAN DOMPET DIGITAL TERHADAP PERILAKU MANAJEMEN KEUANGAN PRIBADI MAHASIWA FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Mawarni Manalu; Yohana Lumbantungkup; Rivani Preselia Br Siringo Ringo; Gilberth Putra Nainggolan (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
This study aims to explore the impact of financial literacy and digital wallet utilization on how students manage their personal finances at the Faculty of Economics, State University of Medan. This study was conducted using quantitative methods, with questionnaires distributed to 45 respondents, and data analysis was performed using multiple linear regression using SPSS software. The findings of this study indicate that financial literacy contributes positively and significantly to students' attitudes towards personal financial management, while digital wallet utilization does not appear to have a significant effect. However, when both variables are analyzed simultaneously, they both have a significant impact, contributing 38.2%. This indicates that financial literacy is a crucial element influencing how students manage their finances, while digital wallet utilization serves as a tool whose effects are highly dependent on how it is used.